1995
DOI: 10.1021/j100018a045
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Temperature Surface Reaction: N2O Formation from NO Dimers at 70 to 90 K on Ag{111}

Abstract: When Ag{ 11 l} is exposed to NO at 40 K, monolayer adsorption is followed by multilayer (N0)z formation. Heating to 60 K results in the desorption of the dimer multilayer, leaving a monolayer on the surface. Using isotopes, the monolayer has also been characterized as dimers, which have the N-N axis coplanar with the surface. At 70 to 90 K, N20 is formed from (N0)2 on the Ag{ 11 11 surface. Further heating to 120 K results in the desorption of the NzO. The reactive species is thus shown to be the adsorbed dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
119
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 9 publications
12
119
0
Order By: Relevance
“…In this pathway, NO reduction proceeds via a "hyponitrite-like" (NO) 2 dimer (Scheme 1b), 20,22,[32][33][34] and, in fact, this intermediate has been detected directly with IR spectroscopy on Ag(111) at low temperatures (70 K). 22,35 (NO) 2 dimers have also been imaged on Cu(110) using scanning tunneling microscopy (STM), 33 and more recently, evidence for the formation (NO) 3 trimers on Cu(111) at 6 K has been collected with STM. 36 Nitric oxide also forms dimers on Pd(111) under certain conditions, as revealed by in situ infrared reflection absorption spectroscopy (IRAS).…”
Section: Introductionmentioning
confidence: 99%
“…In this pathway, NO reduction proceeds via a "hyponitrite-like" (NO) 2 dimer (Scheme 1b), 20,22,[32][33][34] and, in fact, this intermediate has been detected directly with IR spectroscopy on Ag(111) at low temperatures (70 K). 22,35 (NO) 2 dimers have also been imaged on Cu(110) using scanning tunneling microscopy (STM), 33 and more recently, evidence for the formation (NO) 3 trimers on Cu(111) at 6 K has been collected with STM. 36 Nitric oxide also forms dimers on Pd(111) under certain conditions, as revealed by in situ infrared reflection absorption spectroscopy (IRAS).…”
Section: Introductionmentioning
confidence: 99%
“…Infrared spectroscopy was used to identify NO dimers on Ag(111) at temperatures as high as 90 K, and NÀN bond formation to evolve gaseous N 2 O was observed from these dimer precursors. [24,25] The same type of NO dimers on Cu(111) were subsequently observed using infrared spectroscopy. [26] The fact that the condensed-phase type dimers observed on these surfaces have n(NO) vibrational frequencies virtually unperturbed from those of true condensed-phase dimers suggests that their interaction with silver and copper is minimal.…”
Section: Molecular Pathways For No Reductionmentioning
confidence: 61%
“…3 However, formation of N2O on Ag(111) was observed when NO was adsorbed on the surface as low as 80 K. 4 In the case of the NO reaction on MgO, Rodriguez and co-workers suggested that the defective MgO surface was responsible for the production of N2O from NO, 5 while Kim and co-workers reported that more N2O was formed on a "low-defect" MgO surface below 75 K. 6 The anomaly in NO reactivity to form N2O at low temperatures on less-reactive surfaces can be explained by formation of (NO)2. [7][8][9] If the interaction of NO and the surface is week, NO molecules form dimeric NO on the surface. Thermal reaction of (NO)2 produces N2O.…”
Section: Introductionmentioning
confidence: 99%